American Engineering Doctoral Enrollments - Skinner, Richard (International Higher Education, 2013)
International education has deep historical roots and has spurred relationships that persist for decades. In the case of the United States and the field of engineering, American dependence since the mid-1960s on other countries' students especially Indian ones for enrollments and graduates of engineering doctoral programs has been, is and will likely continue to be significant. But long-term trends portend a time when the appeal of American higher education may be less than has been the case.